1999
DOI: 10.1080/00016489950181161
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation for Symptomatic Hereditary Deafness

Abstract: Y. Cochlear implantation for symptomatic hereditary deafness. Acta Otolaryngol (Stockh) 1999; Suppl 540: 34 -37.Recently, the effectiveness of cochlear implantation for hereditary deafness has been reported. We performed cochlear implantation for two patients with symptomatic hereditary deafness. Deafness in one patient was thought to be a result of albinism-deafness syndrome and in the other patient, a result of chronic progressive external ophthalmoplegia syndrome. Since their speech perception abilities imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Previous studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]40,41] and short-term observations in the present study indicate that patients with mtDNA mutations are good candidates for CI. Notably, however, the long-term observations in the present study also suggest that retrocochlear dysfunction may be responsible for the long-term deterioration of speech perception after CI in patients with mtDNA mutations.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]40,41] and short-term observations in the present study indicate that patients with mtDNA mutations are good candidates for CI. Notably, however, the long-term observations in the present study also suggest that retrocochlear dysfunction may be responsible for the long-term deterioration of speech perception after CI in patients with mtDNA mutations.…”
Section: Discussionsupporting
confidence: 64%
“…Cochlear implantation (CI) for patients with severe to profound hearing loss associated with mtDNA mutations has been reported [19,[21][22][23][28][29][30][31][32][33][34][35]. Howes et al [36] reported a case of MIDD with a speech score of 67% at one-month follow-up.…”
Section: Introductionmentioning
confidence: 99%